Art therapy as a professional method of help for cancer patients - Stańko, Maja (Contemporary Oncology/Współczesna Onkologia, 2008)
Cancer diseases are one of the leading causes of death in developing countries. They have both somatic and psychological aspects. They are considered as one of the biggest challenges for contemporary medicine, as well as a severe psychological and social problem. Psychological and emotional problems are closely related to physiological symptoms and they can influence the course of disease. More and more new methods are being developed to help people with cancer problems. One of the most promising methods of psychological aid offered to cancer patients is art therapy. Investigation of the results of art therapy among cancer patients has revealed significant reductions in experienced anxiety and depression, decreased level of stress, and enhancement of self-assessment of global health. The article presents a synthesis of art therapy methods and their results used with oncological patients from the domestic and foreign specialist literature.